Tafsir Ilmi: Sejarah, Paradigma dan Dinamika Tafsir - Mamluatun Nafisah (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
Talking about science and technology, the presence of interpretation with a scientific style has become one of the interpretation trends in the modern and contemporary era. The spread of various interpretive works with a scientific style in the modern-contemporary era is often attributed to the widespread influence of the emergence of Tantawijauhari's (d. 1358 AH/1940 AD) magnum opus, al-Jawāhir fī Tafsīr al-Qur'an al-Karīm. Talking about the dynamics of scientific interpretation in Indonesia continues to develop. In the 1960s, Hasbi ash-Shiddieqiy's tafsir al-Nur began to use scientific discoveries in interpreting several verses of the Koran, although the number was still very small. The 1990s were marked by the spread of books about the relationship between the Koran and science. And in the 2010s, complete works of scientific interpretation have emerged, such as the Scientific Interpretation of Water in the Perspective of the Qur'an and Science, Plants in the Perspective of the Qur'an and Science, and the Apocalypse in the Perspective of the Qur'an and Science which is the work of collaboration between Lajnah Pentashihan Mushaf al-Qur'an, Research and Development and Training Agency of the Ministry of Religion of the Republic of Indonesia and the Indonesian Institute of Sciences (LIPI), and Tafsir Salman Tafsir Ilmiah on Juz 'Amma by ITB scientists and scientists.